A dramatic enhancing effect of InBr3 towards the oxidative Sonogashira cross-coupling reaction of 2-ethynylanilines. Issue 6 (19th January 2016) - Ikeda, A.; Omote, M.; Kusumoto, K.; Komori, M.; Tarui, A.; Sato, K.; Ando, A.
Abstract : A dramatic enhancing effect of InBr3 was observed towards the oxidative Sonogashira cross-coupling reaction of 2-ethynylaniline with ( E )-trimethyl(3, 3, 3-trifluoroprop-1-enyl)silane. Abstract : The addition of InBr3 to the oxidative Sonogashira cross-coupling reaction of 2-ethynylaniline with ( E )-trimethyl(3, 3, 3-trifluoroprop-1-enyl)silane led to a dramatic increase in the reactivity to afford the corresponding 1, 3-enynes bearing a trifluoromethyl group on their terminal sp 2 carbon. The subsequent cyclization of these 1, 3-enynes under palladium catalysis provides access to the corresponding indoles bearing a 3, 3, 3-trifluoroprop-1-enyl group at their 2-position.